Nickel(II)-catalyzed addition of aryl and heteroaryl boroxines to the sulfinylamine reagent TrNSO: the catalytic synthesis of sul-finamides, sulfonimidamides and primary sulfonamides - Lo, PKT; Willis, MC (American Chemical Society, 2021)
We report a redox-neutral Ni(II)-catalyzed addition of (hetero)aryl boroxines to N-sulfinyltritylamine (TrNSO). The reactions use a catalyst generated from the combination of commercial, air-stable NiCl2·(glyme) and a commercially available bipyridine ligand, and deliver sulfinamide products. The scope of the reaction is established using a sulfonimidamide synthesis, in which the initially formed sulfinamides undergo oxidative chlorination with the inexpensive and safe chlorinating agent, trichloroisocyanuric acid (TCCA), to produce sulfonimidoyl chlorides as key intermediates. These are combined in situ with a range of amines to deliver sulfonimidamides. The sulfonimidoyl chlorides can also be elaborated into primary sulfonamides via hydrolysis, and sulfonimidoyl fluorides via treatment with fluoride. These transformations are all achieved using one-pot procedures. Unprotected, primary sulfinamides are also available. For larger-scale reactions, the catalyst loading can be reduced to 1 mol %.